Kemudahan Akses Kutipan Buku Leter C Sebagai Bukti Kepemilikan Hak Atas Tanah Oleh Pemerintah Desa - Laila, Khotbatul (Legal Spirit, 2023)
Ease of access to land letter C book excerpts as proof of ownership of land rights by the village government in the context of public information disclosure. The research method uses empirical legal research with a sociological juridical approach. The results of the research show that in providing easy access to quotations from letter C books as proof of ownership of land rights by the village government in the context of public information disclosure, the village government is guided by the provisions of the applicable laws and regulations, although still in a conventional way, namely based on a letter of application from the applicant and then the village government issues a land history statement based on the letter C book in the village to be given to the applicant provided that the applicant is a party who has a legal relationship with the object for which the letter C quotation is requested. If these requirements are not met, the village government will not issue the requested Letter C quotation, except by order of the court. The obstacles faced by the village government in providing easy access to quotations from the letter C book as proof of ownership of land rights in order to realize openness of public information and alternative solutions are the disorderly administration of the village government, especially in the village letter C book, data (information) in the letter C book. but it does not match the reality and the condition of the Letter C book is outdated (difficult to read) as well as political differences during the village head election. Alternative solutions include encouraging PTSL programs in villages, digitizing letter C books, providing outreach to the community about the importance of title ownership certificates as proof of legal ownership.